Interactive Multimedia Based on Problem Based Learning Models on Material Changes in the form of Objects - Ni Made Sita Rahayu; I Gusti Ayu Tri Agustiana (Mimbar Ilmu, 2023)
Science learning requires media to support the delivery of generally abstract material that becomes concrete. Media use is limited and less varied, so demand and student learning outcomes decrease. This study aims to develop interactive multimedia based on problem-based learning on material changes in the form of objects in grade V elementary schools that are valid, practical, and effective. This research belongs to the development research developed with the ADDIE model. The data collection methods used are questionnaires, observations, and tests. The data obtained in the study were then analyzed using qualitative and quantitative data analysis techniques. The results of development research through validity testing from material experts were 96.67%, learning design experts 94.23%, media experts 93.33%, individual trials 93.89%, and small group trials 90.55%; the practicality test of student responses was 89.12%, and the observation of the implementation of learning activities was 93.33%. The result of the effectiveness test is that there is a significant difference in students' science cognitive learning outcomes before and after using interactive multimedia based on problem-based learning, so interactive multimedia is effectively used to improve student learning outcomes. It was concluded that interactive multimedia based on problem-based learning is valid, practical, and effective when applied to natural science content material for changes in the shape of objects for fifth-grade elementary school students.